2018
DOI: 10.1097/psy.0000000000000610
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Daily Stress on Sedentary Behavior: Group and Person (N of 1) Level Results of a 1-Year Observational Study

Abstract: These findings suggest that the influence of stress on sedentary behavior varies by source of stress and from person to person. A precision medicine approach may be warranted to target reductions in sedentary time, although further studies are needed to confirm the observed findings in light of study limitations including a small sample size and enrollment of participants from a single, urban metropolitan area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 42 publications
2
20
0
Order By: Relevance
“…Four studies were longitudinal [33, 38, 45, 55] ( n = 271 to 11,676), two were controlled clinical trials [39, 48] ( n = 43–231), two were pilot interventions [40, 52] ( n = 12 to 20) and two were direct observation studies (i.e. where time in sedentary behaviour was collected for one year or one month and averaged) [33, 37] ( n = 79 to 140). The majority of these studies were conducted in Australia ( n = 8) and the US ( n = 8).…”
Section: Resultsmentioning
confidence: 99%
“…Four studies were longitudinal [33, 38, 45, 55] ( n = 271 to 11,676), two were controlled clinical trials [39, 48] ( n = 43–231), two were pilot interventions [40, 52] ( n = 12 to 20) and two were direct observation studies (i.e. where time in sedentary behaviour was collected for one year or one month and averaged) [33, 37] ( n = 79 to 140). The majority of these studies were conducted in Australia ( n = 8) and the US ( n = 8).…”
Section: Resultsmentioning
confidence: 99%
“…Whilst this is thought to be the first study to explore the relationship between hair cortisol levels and device-based measures of occupational sitting patterns, previous studies employing self-reported measures of these outcomes have reported similar findings [19,20]. For example, although they used self-reported sedentary behaviour in different context (not specifically occupational sitting) and reported on a different population ( n = 72 women from low socio-economic areas of Australia as opposed to a more educated working population in Scotland), Teychenne et al (2018) found no relationship between self-reported TV viewing time, computer usage or overall sitting and hair cortisol levels [20].…”
Section: Discussionmentioning
confidence: 74%
“…Knowing more details about the source of stress might therefore be important. This idea is alluded to in a recent study by Diaz et al (2018) [19]. In this N of one, yearlong observational study (a type of statistical modelling that determines associations at an individual level and accounts for individual variability) [35], they assessed device recorded sedentary behaviour, a global measure of stress (self-reported end of day stress) and source specific stress (including running late for work) in 79 healthy working adults in America.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations